CYP1A1 and CYP2E1 polymorphism frequencies in a large Brazilian population - Renata dos Santos Coura; Christiane de Fátima Silva Marques; Rosalina J. Koifman; Sergio Koifman; Pedro Hernan Cabello; Ana Hatagima (Genetics and Molecular Biology, 2007)
The enzymes encoded by the polymorphic genes CYP1A1 and CYP2E1 play an important role in the activation and inactivation of xenobiotics. These enzymes have been associated with xenobiotic-induced diseases, such as cancer, therapeutic failure and adverse effects of drugs. The aim of the present study was to determine the allelic and genotypic frequencies of these polymorphisms in a large, ethnically mixed Brazilian population sample from Rio de Janeiro. Polymorphisms CYP1A1 and CYP2E1 were determined in 870 unrelated individuals by PCR-RFLP analysis in peripheral blood DNA. The observed allelic frequencies were 0.90 for CYP1A1*1A and 0.95 for CYP2E1*1A, in the total sample. The allelic frequency of CYP1A1*2C in "pardos" (0.13) and Brazilian whites (0.11) was higher than in Caucasians (0.05), which may be a result of the Amerindian genetic component, that presents the highest frequency of this allele observed up to now. The genotype distributions for both polymorphisms were in Hardy-Weinberg equilibrium and were statistically different between males and females, and among ethnic groups.